The effect of Qur'anic Healing on reducing the frequency of Auditory Hallucination Rating Scale (AHRS) in schizophrenia - Muhammad Rosyidul Ibad; Febry Syaren Alfianti; Muhammad Ari Arfianto; Tutu April Ariani; Zahid Fikri (PAGEPress Publications, 2024)
Auditory hallucinations have led to decreased productivity, impaired interaction, and diminished well-being in individuals with schizophrenia. However, the challenge lies in enabling patients to independently manage their hallucinations, and one potential approach is through psycho-religious methods utilizing the Qur'an. This study aimed to assess the impact of Qur'anic healing on reducing the frequency of auditory hallucinations in individuals with schizophrenia. Employing a quasi-experimental design with a one-group pre-post-test, this study included 35 respondents selected through purposive sampling. Inclusion criteria stipulated that participants must have a diagnosis of schizophrenia accompanied by auditory hallucinations, coherent thinking, a cooperative attitude, and adherence to the Muslim faith. The Auditory Hallucination Rating Scale (AHRS) served as the instrument for data collection, with analysis conducted using the Wilcoxon test. The findings revealed a significant effect of Qur'anic healing on reducing the frequency of auditory hallucinations, indicated by a p-value of 0.000 (p<0.05). Qur'anic healing demonstrated effectiveness in alleviating auditory hallucinations among individuals with schizophrenia. We recommend incorporating Qur'anic healing as an additional supportive therapy for schizophrenia patients. Moreover, it is anticipated that listening to Qur'anic healing will enhance the patient's adaptive coping mechanisms.